Identifikasi Status Hara Tanah pada Lahan Kering sebagai Dasar Pemupukan Kedelai di Kecamatan Andoolo Kabupaten Konawe Selatan - Musyadik, Musyadik (Jurnal Ecosolum, 2019)
Soybean is a potential type of legume plant to be developed in Andoolo District, South Konawe Regency. However, the soybeans production is still relatively low. The main problem in the low production of soybeans is the unavailability of information on soil fertility status, especially the status of organic C-nutrients, P and K. Therefore information on soil nutrient status is very necessary. The study was conducted in the village of Ataku, Andoolo District, South Konawe Regency in May to July 2018 using the Dry Soil Test Equipment (PUTK) method. There were 27 soil samples taken randomly to obtain soil nutrient status including organic matter, P, K and soil pH and recommendations for soybean fertilizer dosages in the Andoolo District. The results of this study showed that C-Organic status, P, K and pH in Andoolo District varied. Based on the results of the analysis, the recommended fertilizer dosage in Andoolo District is giving 2 tons/ha of organic matter plus 200 kg/ha of Urea fertilizer, 200 kg/ha of SP36, and 100 kg/ha of KCl for low K status, 75 kg/ha of KCl for moderate K status and 50 kg/ha of KCl for soil with high K status. For soil with a very acidic and acidic pH status, it is recommended to give 500 kg/ha of lime doses to increase the soil pH to neutral conditions.